HUBUNGAN PENYULUHAN SEKOLAH LAPANG TERHADAP PERILAKU PETANI PADI ORGANIK DI KECAMATAN BUAY MADANG - Arbi, Muhammad; Ritonga, Utan Sahiro; Yamin, M.; Putri, Nurilla Elsya (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2026)
This study aims to analyze the relationship between the implementation of Field School Extension (PSL) and the behavior of organic rice farmers in Sumber Mulyo Village, Buay Madang Timur District, Ogan Komering Ulu Timur Regency, South Sumatra. The study used a quantitative approach with a survey method. A sample of 40 organic rice farmers was taken from four farmer groups (10 respondents each) through a cluster stratified sampling technique. Data were collected using questionnaires and interviews. Data analysis was carried out by scoring to assess the implementation of PSL including the procurement of tools and inputs, organic materials, field school training, field laboratories, and field school practices as well as scoring farmer behavior including knowledge, attitudes, and skills. The relationship between PSL implementation and farmer behavior was tested using the Chi-Square test. The results showed that the implementation of PSL was classified as high (total score 25.72) and farmer behavior was also in the high category (total score 170.93; knowledge 56.53; attitude 57.31; skills 57.09). The Chi-Square test yielded a Pearson Chi-Square of 29.162 (df=4) with a significance value of p=0.000 (<0.05), indicating that the implementation of PSL is significantly related to the behavior of organic rice farmers. In conclusion, strengthening and sustaining PSL has the potential to maintain and improve farmers' organic rice cultivation behavior.